Transport, Fluids, and Mixing - Crippa, Gianluca (De Gruyter, 2018)
The aim of this volume is to present the state of the art in the mathematical analysis of transport and mixing phenomena in fluids and associated problems. It supplements current literature on the subject with a unique blend of contributions that touch upon both theoretical as well as modeling questions and showcase a variety of techniques, from the analysis of partial differential equations, to harmonic analysis, to computational methods. The volume contains the expanded notes from lectures by leading experts in the field at the Summer School Transport, Fluids, and Mixing held in Levico Terme, Italy, July 19